Brushless DC Motor Speed Control based on PID-Fuzzy Controller - Ahmad Sobri, Muhammad Hanafi Adli; Dur Muhammad Soomro (Evolution in Electrical and Electronic Engineering, 2022)
Brushless DC (BLDC) motors provide numerous advantages, including improved efficiency and lower maintenance requirements as compared to conventional DC motors. The demand for BLDC motors in the industry for a variety of applications is increasing over time. In order to meet the demands of users and industry, BLDC motors must be improved. The issue with BLDC motors is that they cannot run effectively when employing a certain controller in a non-linearity condition or application. The proposed methodology for this study is a PID-Fuzzy controller for controlling the speed of a BLDC motor. This paper comparing between standard PID and PID-Fuzzy controller-based speed control. Digital simulation in MATLAB/Simulink is used to analyze the efficiency of the BLDC motor speed. In conclusion, is that the PID-Fuzzy controller approach is the best for managing the speed of BLDC motors since it produces better outcomes than other methods. The outcomes of this research indicate that the PID-Fuzzy controller is better than the PID controller in terms of its ability to manage the speed of the BLDC motor and reduce the amount of settling time necessary to achieve the target speed.